Pemberdayaan sebagai Upaya Peningkatan Konservasi Budaya Lokal di Desa Menari Tanon - Lestari, Tutik Sri; Suminar, Tri (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan Universitas Negeri Semarang, 2020)
This study aims to describe the planning, implementation, results, and supporting and inhibiting factors of community empowerment in Tanari Menari Village. This research method is a qualitative approach. The research subjects consisted of the head of the Pokdarwis, community leaders, dancers, tour guides, and traders. Data collection techniques through observation, interviews and documentation. Data validity uses triangulation of sources, methods and theories. Data analysis techniques through data reduction, data presentation and conclusion drawing. The results of the study revealed that the planning stage was carried out by the chairman of the Pokdarwis and Astra. Implementation of activities with training and community training. As a result of empowerment the Tanon community was able to play a role according to their ability, and the community was able to improve the economy. Supporting factors include economic needs, community awareness of preserving superior local potential, and interest in activities according to their abilities. And the inhibiting factors are the dancers are not consistent in a long time, the facilities and infrastructure are not complete, there are still residents who are not aware of tourism.